STUDI ADSORPSI LOGAM Pb(II) DAN Cd(II) PADA ASAM HUMAT DALAM MEDIUM AIR - Rahmawati, Atik; Santoso, Sri Juari (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2012)
It had been conducted a study on adsorption of Cd (II) and Pb (II) of humic acid isolated from peat soil from village of Sambutan, the subdistrict of Samarinda Ilir, East Kalimantan. Aspects studied covered adsorption kinetics and adsorption isotherm of Cd (II) and Pb (II) of humic acid in water medium.Adsorption process carried out by batch method. Kinetics study conducted by intracting metal adsorption of Cd (II) and Pb (II) with humic acid at various times, meanwhile studying the adsorption isotherm is done by interacting Cd (II) and Pb (II) at various concentrations with humic acid.The results showed the adsorption rate of Cd (II) and Pb (II) on humic acid followed first order with rate constants of Cd (II) and Pb (II) of 0.0012 and 0.0038 mg menit-1/10 humic acid. Carboxylic groups of humic acid as the main groups which were actively involved in the interaction of metal-humic acid and have experienced deprotonation isÂ hard nucleophile. It made Pb (II) was more quickly and easily adsorbed than Cd (II). Adsorption isotherm of Cd (II) and Pb (II) on humic acid followed the pattern of Langmuir isotherm with adsorption capacities of Pb (II) of 1.66 x10-3 mol / g and for Cd (II) 3.83 x10-3 mol / g . The adsorption energy of both metals is relatively small that is equal to 16.1 for Cd(II) and 21.4 kJ / mol for Pb(II).